Co-micronized Palmitoylethanolamide/Polydatin Treatment Causes Endometriotic Lesion Regression in a Rodent Model of Surgically Induced Endometriosis - Di Paola, Rosanna; Fusco, Roberta; Gugliandolo, Enrico; Crupi, Rosalia; Evangelista, Maurizio; Granese, Roberta; Cuzzocrea, Salvatore (Frontiers in Pharmacology, 2016)
Endometriosis is a chronic, painful disease characterized by the presence of endometrial glands and stroma outside the uterine cavity. Palmitoylethanolamide (PEA), an endogenous fatty acid amide, has anti-inflammatory and neuroprotective effects. PEA lacks free radical scavenging activity, unlike polydatin (PLD), a natural precursor of resveratrol. The aim of this study was to investigate the effect of orally administered co-micronized PEA/polydatin [m(PEA/PLD)] in an autologous rat model of surgically induced endometriosis. Endometriosis was induced in female Wistar albino rats by auto-transplantation of uterine squares (implants) into the intestinal mesentery and peritoneal cavity. Rats were distributed into one control group and one treatment group (10 animals each): m(PEA/PLD) 10 mg/kg/day. At 28 days after surgery the relative volume of the endometrioma was determined. Endometrial-like tissue was confirmed by histology: Masson trichrome and toluidine blue were used to detect fibrosis and mast cells, respectively. The treated group displayed a smaller cyst diameter, with improved fibrosis score and mast cell number decrease. m(PEA/PLD) administration decreased angiogenesis (vascular endothelial growth factor), nerve growth factor, intercellular adhesion molecule, matrix metalloproteinase 9 expression, and lymphocyte accumulation. m(PEA/PLD) treatment also reduced peroxynitrite formation, (poly-ADP)ribose polymerase activation, IkBα phosphorylation and nuclear facor-kB traslocation in the nucleus. Our results suggested that m(PEA/PLD) may be of use to inhibit development of endometriotic lesions in rats.